Expression of desmosomal proteins and their implications during enamel organ morphogenesis - Hadi BILAL (Wolters Kluwer Medknow Publications, 2018)
Background/Objective: The present article is between the fewest that describe the expression of desmosomal proteins in human tooth organ and to implicate desmosome and its components in tooth morphogenesis. Although present in all epithelia, desmosomes are particularly down regulated in undifferentiated, dedifferentiated and malignant cells. Methodology: In the present article, using immunohistochemical staining, we report the expression patterns of 6 desmosomal components; Desmoplakin, plakoglobin, desmoglein, plakophilin-1, plakophilin-2, and plakophilin-3. The dental, oral and ectodermal epithelia were investigated in 7 and 9 weeks' human embryos. Results: The expression of these components appeared to associate with cell differentiation, stage of development and epithelial type. The fundamental desmosomal proteins, desmoplakin, plakoglobin and desmoglein, produced almost identical profiles, suggesting that desmosomes are absent or under developed in negative and weak reacting areas respectively. Whilst the accessory component plakophilin-1 was always absent, plakophilin-2 and -3 were strongly labeled in the embryonic epidermis and moderately expressed in the oral epithelium. In the developing enamel organ, gradients of fundamental protein expressions were produced being strong towards the oral epithelium and weak/negative around the inner enamel epithelium. These gradients were also produced using antibodies to plakophilin-2 and -3 although the majority of enamel organ cells were unlabeled. Conclusion: Mirror image symmetry was foundwas found for the distribution patterns of these markers. Furthermore, the left-right asymmetry was found both for the maxillary and mandibular tooth germs, thus bringing further evidence implicating desmosome and its components in the mechanisms regulating tooth morphogenesis.